2013
DOI: 10.1111/j.1756-1051.2012.01724.x
|View full text |Cite
|
Sign up to set email alerts
|

Pradosia restingae sp. nov. from the Atlantic forest, Brazil

Abstract: Pradosia restingae Terra‐Araujo, a new species of Sapotaceae (Chrysophylloideae) from the Brazilian Atlantic forest is described and illustrated. It is only known from the southern coast of the State Rio Grande do Norte and is likely restricted to the coastal sand dune ecosystem, locally known as the restinga forest, from which the epithet is derived. The species is naturally common, but due the low number of known subpopulations we assign P. restingae a preliminary conservation status of ‘Endangered’ (EN).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…1L-M), which is absent in the rest of the subfamily (Terra-Araujo et al, 2013). The genus varies in habit from geoxylic shrubs (one species) to medium-sized and large trees.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…1L-M), which is absent in the rest of the subfamily (Terra-Araujo et al, 2013). The genus varies in habit from geoxylic shrubs (one species) to medium-sized and large trees.…”
Section: Introductionmentioning
confidence: 98%
“…Species are distributed across a wide variety of habitats, including savannahs and evergreen to deciduous forests in the Amazon region, the Brazilian Atlantic coast, and the Andes. The Amazon and Atlantic coast are the two major centres of diversity for Sapotaceae (Pennington, 1990;Alves-Araújo and Alves, 2011;Terra-Araujo et al, 2013), where 80% of the species occur. The biogeographical connections between these regions are still poorly understood and, to date, only a handful of studies have estimated divergence times between taxa from these regions, finding that organisms in the two areas have been isolated from each other for several million years (Vicentini, 2007;Fiaschi and Pirani, 2009;Pellegrino et al, 2011;Fouquet et al, 2012a,b).…”
Section: Introductionmentioning
confidence: 99%
“…However, the knowledge of RN’s flora is growing rapidly. New species have recently been discovered (Sobral 2010, Araújo and Alves 2013, Lourenço et al 2013, Terra-Araújo et al 2013, Ribeiro et al 2015b, Souza et al 2016) and new occurrences for genera or species have been reported for RN (Versieux et al 2013a, 2013b, São-Matheus et al 2013, Magalhães et al 2014, Amorim et al 2016, Colombo et al 2016, Gomes-Costa and Alves 2016). In five years, the number of species records for RN increased by 78% (BFG 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular data. -Sequence data from the nuclear ribosomal DNA (ETS, ITS) and the nuclear gene RPB2 were used since they have proven to provide ample information for phylogenetic inference in Sapotaceae at all taxonomic levels (Swenson & al., , 2019Terra-Araujo & al., 2015;Faria & al., 2017). Also, since Gayella is a member of the well-known Australasian clade (Bartish & al., 2005;Swenson & al., 2008bSwenson & al., , 2014Swenson & al., , 2019, existing sequence data was used and assembled into matrices using AliView v.1.26 (Larsson, 2014), manually checked, adjusted and subsequently prepared in BEAUti v.1.10.4 (part of the BEAST package) to an input xml-file for Bayesian inference.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%